(untitled) (International Journal of Nursing Education, 2019)
The vision for the future of nursing has led to convergence of knowledge, quality, and new functions in nursing that require new competencies beyond evidence-based practice (EBP). However, the success of teaching and implementing EBP rely on the competencies of nursing educators. This study aimed to determine the effectiveness of the Evidence-Based (EBP) Training Program in enhancing the EBP competencies of faculty members. An EBP Training Program was conducted among 13 nurse educators. The participants cognitive and psychomotor competencies were measured before and after the EBP Training Program using a self-made cognitive and psychomotor competency questionnaire. Pre-test and post-test scores were then analyzed using RM-MANOVA. Results revealed that the EBP Training Program caused a large improvement in the cognitive competency in EBP of nurse educators. However, the training program was not sufficient to cause a significant effect on the psychomotor competency of the nurse educators.